The Relationship Between Hydration Status and Electrolyte Status of ICU Patients Dr. H. Soemarno Sosroatmodjo Hospital - Semly, Debora; Abdurrachim, Rijanti; Nurhamidi (Jurnal Riset Pangan dan Gizi, 2025)
ICUs treat critically ill patients at high risk of hydration and electrolyte disturbances, which can prolong the length of stay and increase mortality. Data from Dr. H. Soemarno Sosroatmodjo Kuala Kapuas Hospital shows a prevalence of electrolyte disturbances of 43.6%, hydration disturbances of 26.9%, and an ICU mortality rate of 30%. Suboptimal hydration monitoring often causes imbalances to go undetected. This study aims to examine the relationship between hydration and electrolyte status and length of stay in ICU patients to improve the quality of care and patient outcomes. This study used an observational analytical design with a prospective and cross-sectional approach. The population consisted of all ICU patients at Dr. H. Soemarno Sosroatmodjo Kuala Kapuas Hospital, with 19 samples taken by total sampling. Data were obtained from medical records and analyzed using the Pearson Rank correlation test. The results of the analysis showed no significant relationship between hydration status and sodium levels (r = -0.012; p = 0.961) and potassium, with an average sodium level of 140.421 and potassium 3.694 within the normal range. The study concluded that changes in hydration status did not significantly affect sodium and potassium levels in ICU patients. Suggestions for further research are for primary data for calculating input and output fluids.